PENCITRAAN TOKOH SRI NINGSIH DALAM NOVEL TENTANG KAMU KARYA TERE LIYE: PENDEKATAN PSIKOLOGI SASTRA - Fadriani, Rizki; Seli, Sisilya; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractImagery figures are portrayals physically, psychically, and social aspects or images of shadings, fantasies, or concepts. The problem in this research is the way the author describes the physical image of the character, the psychic image of the character, the image of the figure in the social aspect seen from the study of literature psychology, and how the implementation plan of research results in the Tere Liye?s novel Tentang Kamu. This research is qualitative, using descriptive method and literary psychology approach. The data source is Tere Liye's novel Tentang Kamu. Data collection techniques used in this study is a documentary study technique, while the data collection tool in this study is the author. Techniques test the validity of data with observational persistence and reference adequacy. Data analysis technique used in this research is based on psychology literature approach. Based on the results of data analysis on Tere Liye's novel Tentang Kamu work can be concluded. That the character of Sri Ningsih has a short body, stocky, and dark skin. Sri Ningsih is an eccentric, patient, positive-minded person, a strong person, hardworking, always happy, innocent and consistent, diligent, and calm and peaceful. Everyone she encounters has been love her.  Keywords: Novel, Imagery, and Figure.